1994
DOI: 10.1002/jbm.820280111
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage/particle interactions: Effect of size, composition and surface area

Abstract: Particulate wear-debris are detected in histiocytes/macrophages of granulomatous tissues adjacent to loose joint prostheses. Such cell-particle interactions have been simulated in vitro by challenging macrophages with particles dosed according to weight percent, volume percent, and number of particles. Each of these dosage methods has inherent shortcomings due to varying size and density of challenging particles of different compositions. In this study we challenged P388D1 macrophages with titania and polystyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
228
0
6

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(246 citation statements)
references
References 23 publications
12
228
0
6
Order By: Relevance
“…Our study extends these results and shows for the first time that not only TiAlV-, mixed-, or PMMA-particles [35,40], but also polyethylene-particles induce an activation of NF-KB signalling and the TNFa-promoter. Numerous studies of wear debris from periprosthetic tissues have underlined the key role of PE-particles demonstrating that 70-90% of the recovered particles are submicrometer polyethylene-particles [12, 24,34,46,47]. Metal-on-polyethylene and ceramic-on-polyethylene components are the most common bearing surfaces used in joint replacement leading predominantly to generation of polyethylene-particles.…”
Section: Discussionmentioning
confidence: 99%
“…Our study extends these results and shows for the first time that not only TiAlV-, mixed-, or PMMA-particles [35,40], but also polyethylene-particles induce an activation of NF-KB signalling and the TNFa-promoter. Numerous studies of wear debris from periprosthetic tissues have underlined the key role of PE-particles demonstrating that 70-90% of the recovered particles are submicrometer polyethylene-particles [12, 24,34,46,47]. Metal-on-polyethylene and ceramic-on-polyethylene components are the most common bearing surfaces used in joint replacement leading predominantly to generation of polyethylene-particles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that cells were sensitive to the surface of material present in the cell culture [10,[24][25].…”
Section: Particles Characteristicsmentioning
confidence: 99%
“…To date, methods developed to assess the biologic reactivity to wear debris have considered the sizes, compositions, and surface areas of the particles [22,30,33,44,45]. However, a careful reevaluation of the biologic activity for crosslinked PE should take into account the overall volume in addition to the particle size, composition, and area and should be based on a highly precise method for obtaining purified and well-characterized PE particles.…”
Section: Introductionmentioning
confidence: 99%